Development of an Integrated Scheduling System Prototype at the Department of Electrical Engineering Education, Makassar State University - Dessy Ana Laila Sari (Fakultas Teknik Universitas PGRI Banyuwangi, 2022)
This study aims to produce a prototype of an integrated scheduling system that manages all activities related to scheduling within the Department of Electrical Engineering Education, Makassar State University. An integrated scheduling information system was developed using the Research and Development (R&D) research method by collecting data from observation and interviews. The prototype development model is carried out in various integrated stages so that a web-based scheduling system design is obtained with the aim of providing optimal services to lecturers and students so that lecture activities can run well and effectively..